Pelatihan Teknik dan Isi Pesan dalam Poster Digital - Ashar Banyu Lazuardi; Risyaf Kudus Pranasa; I Gede Anjas Kharisma Nata; I Nyoman Miyarta Yasa; Irfan Hidayat (Insan Kreasi Media, 2023)
The problem found in the environment of SMP Negeri 1 Gerung is the lack of understanding of students in using or exploiting digital media as an effective learning tool, especially in the field of graphic design, which is currently the promotional media with the greatest use in society. This training was carried out with the aim of providing insight and experience for students so they know better how to use digital media properly and correctly. This training focuses on understanding and how to create poster designs using currently available digital media. For students, this training is very necessary so that they can use digital media professionally. The expected benefit is that students are able to understand and create poster designs by utilizing existing digital media and can broaden their horizons in graphic design science. The method in this activity is to provide material and design training using vector and bitmap image processing software, by providing understanding and training about poster graphic design that students can use, starting from providing an understanding of posters, showing what is needed to make a poster, and train how to make posters and how to use posters. The result of this activity is that students understand and are able to make posters and can utilize the posters they make. This activity also provides benefits for the teachers of SMP Negeri 1 Gerung who participated in the training, to be able to implement the knowledge they have to students and the wider community.